Immunogenicity of SARS-CoV-2 vaccination in patients undergoing autologous stem cell transplantation. A multicentric experience - Autore, Francesco; Stirparo, Luca; Innocenti, Idanna; Papa, Elena; Marchesi, Francesco; Togni, Chiara; Mariani, Sabrina; Torrieri, Lorenzo; Salvatori, Martina; Fazio, Francesca; Metafuni, Elisabetta; Giammarco, Sabrina; et al. (Frontiers in Oncology, 2022)
COVID-19 disease has a strong impact on hematological patients; those receiving autologous haematopoietic stem cell transplantation (aHSCT) represent a particularly vulnerable group, in which the effectiveness of vaccination is very variable. Chiarucci et al showed that patients affected by Non-Hodgkin lymphoma (NHL) and treated with Rituximab experienced lower rate of immunization against SARS-CoV-2 (54%) and significantly lower IgG antibodies titer. In our multicenter retrospective observational study, we included 82 patients who underwent aHSCT, divided in two groups: 58 patients vaccinated after aHSCT (group A) and 24vaccinated before getting transplantation (group B). In group A 39 (67%) patients had a positive serology and the rate of positivity increased with time from the aHSCT. In the subgroup of patients with NHL, the administration of Rituximab predicted negative serology, particularly when administered in the six months before vaccination (13% response rate). Patients affected by plasma cell s had a higher rate of positivity (83% overall), independently from the time to aHSCT. In group B, no patient who initially showed positive serology became negative after the transplantation, so the aHSCT did not affect the response to the vaccination. Our study confirmed the role of Rituximab as negative predictor of response to SARS-CoV-2 vaccination, whereas the conditioning and transplantation procedure itself seemed to be less important.